K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

10 tháng 9 2020

( x - 1 )3 + 3x( x - 4 ) + 2 = 0

<=> x3 - 3x2 + 3x - 1 + 3x2 - 12x + 2 = 0

<=> x3 - 9x + 1 = 0

Chịu :))

10 tháng 9 2020

Mình sửa đề 1 chút\(\left(x-1\right)^3+3x\left(x-4\right)+1=0\)

\(\Leftrightarrow x^3-3x^2+3x-1+3x^2-12x+1=0\)

\(\Leftrightarrow x^3-9x=0\)

\(\Leftrightarrow x\left(x^2-9\right)=0\)

\(\Leftrightarrow\orbr{\begin{cases}x=0\\x^2-9=0\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=0\\x=\pm3\end{cases}}\)

2 tháng 7 2018

(x+2)(x+3)-(x-2)(x+5)=0

=> x2+5x+6-x2-3x+10=0

=>2x+16=0 

 =>2x=-16

=>x=-8

27 tháng 8 2018

a)  \(x^3+3x^2+3x+2=0\)

<=>  \(x^3+x^2+x+2x^2+2x+2=0\)

<=>  \(x\left(x^2+x+1\right)+2\left(x^2+x+1\right)=0\)

<=>  \(\left(x+2\right)\left(x^2+x+1\right)=0\)

tự làm

b) \(x^4-2x^3+2x-1=0\)

<=>  \(\left(x^4-3x^3+3x^2-x\right)+\left(x^3-3x^2+3x-1\right)=0\)

<=>  \(x\left(x^3-3x^2+3x-1\right)+\left(x^3-3x^2+3x-1\right)=0\)

<=>  \(\left(x^3-3x^2+3x-1\right)\left(x+1\right)=0\)

<=>  \(\left(x-1\right)^3\left(x+1\right)=0\)

tự làm

27 tháng 8 2018

c)   \(x^4-3x^3-6x^2+8x=0\)

<=>   \(x\left(x^3-3x^2-6x+8\right)=0\)

<=>  \(x\left[\left(x^3+x^2-2x\right)-\left(4x^2+4x-8\right)\right]=0\)

<=>\(x\left[x\left(x^2+x-2\right)-4\left(x^2+x-2\right)\right]=0\)

<=>   \(x\left(x-4\right)\left(x^2+x-2\right)=0\)

<=> \(x\left(x-4\right)\left(x-1\right)\left(x+2\right)=0\)

tự làm

30 tháng 8 2016

Chử đề sai câu 1:

1, x(x-2)+x-2=0

28 tháng 7 2021

bạn đăng tách ra nhé

a, \(\left(2x+1\right)\left(x-4\right)=\left(2x+1\right)^2\)

\(\Leftrightarrow2x^2-7x-4=4x^2+4x+1\Leftrightarrow2x^2+11x+5=0\)

\(\Leftrightarrow\left(x+5\right)\left(2x+1\right)=0\Leftrightarrow x=-5;x=-\frac{1}{2}\)

b, sửa đề :  \(\left(x-4\right)\left(x^2+4x+16\right)-\left(x^2-6\right)=2\)

\(\Leftrightarrow x^3-64-x^2+6=2\Leftrightarrow x^3-x^2-60=0\Leftrightarrow x=4,27...\)

c, \(\left(2x-1\right)^2-\left(3x+4\right)^2=0\Leftrightarrow\left(2x-1+3x+4\right)\left(2x-1-3x-4\right)=0\)

\(\Leftrightarrow\left(5x+3\right)\left(-x-5\right)=0\Leftrightarrow x=-\frac{3}{5};x=-5\)

d, \(\left(9x+2\right)\left(x-1\right)-\left(3x-1\right)^2=0\)

\(\Leftrightarrow9x^2-7x-2-9x^2+6x-1=0\Leftrightarrow-x-3=0\Leftrightarrow x=-3\)

28 tháng 7 2021

e, \(\left(2x+3\right)^2-4\left(x-1\right)\left(x-1\right)\left(x+1\right)=0\)

\(\Leftrightarrow4x^2+12x+9-4\left(x-1\right)\left(x^2-1\right)=0\)

\(\Leftrightarrow4x^2+12x+9-4\left(x^3-x-x^2+1\right)=0\)

\(\Leftrightarrow4x^2+12x+9-4x^3+4x+4x^2-4=0\)

\(\Leftrightarrow-4x^3+8x^2+16x+5=0\Leftrightarrow x=-0,9...;x=-0,41...;x=3,31...\)

f, \(15x\left(x+4-6x-24\right)=0\Leftrightarrow15\left(-5x-20\right)=0\)

\(\Leftrightarrow-75x-300=0\Leftrightarrow x=-4\)

g, \(\left(4x-10\right)\left(2-3x\right)-30^2=0\)

\(\Leftrightarrow8x-12x^2-20+30x-900=0\Leftrightarrow-12x^2+38x-920=0\)

vô nghiệm 

19 tháng 7 2018

a) 5xy ( x - y ) - 2x + 2y

= 5xy ( x - y ) - 2 ( x - y )

= ( x - y ) ( 5xy - 2 )

b) 6x-2y-x(y-3x)

= 2 ( y - 3x ) - x ( y - 3x )

= ( y - 3x ( ( 2 - x )

c)  x+ 4x - xy-4y

= x ( x + 4 ) - y ( x + 4 )

( x + 4 ) ( x - y )

d) 3xy + 2z - 6y - xz 

= ( 3xy - 6y ) + ( 2z - xz )

= 3y ( x - 2 ) + z ( x - 2 )

= ( x - 2 ) ( 3y + z )

19 tháng 7 2018

a,5xy(x-y)-2x+2y=5xy(x-y)-2(x-y)=(x-y)(5xy-2)

b,6x-2y-x(y-3x)=-2(y-3x)-x(y-3x)=(y-3x)(-2-x)

c,x^2+4x-xy-4y=x(x+4)-y(x+4)=(x+4)(x-y)

d,3xy+2z-6y-xz=(3xy-6y)+(2z-xz)=3y(x-2)+z(2-x)=3y(x-2)-z(x-2)=(x-2)(3y-z)

11)

a,4-9x^2=0

(2-3x)(2+3x)=0

2-3x=0=>x=2/3 hoặc 2+3x=0=>x=-2/3

b,x^2 +x+1/4=0

(x+1/2)^2 =0

x+1/2=0

x=-1/2

c,2x(x-3)+(x-3)=0

(x-3)(2x+1)=0

x-3=0=>x=3 hoặc 2x+1=0=>x=-1/2

d,3x(x-4)-x+4=0

3x(x-4)-(x-4)=0

(x-4)(3x-1)=0

x-4=0=>x=4 hoặc 3x-1=0=>x=1/3

e,x^3-1/9x=0

x(x^2-1/9)=0

x(x+1/3)(x-1/3)=0

x=0 hoặc x+1/3=0=>x=-1/3 hoặc x-1/3=0=>x=1/3

f,(3x-y)^2-(x-y)^2 =0

(3x-y-x+y)(3x-y+x-y)=0

2x(4x-2y)=0

4x(2x-y)=0

x=0hoặc 2x-y=0=>x=y/2

29 tháng 9 2017

b,   <=> (x-1)(3x+7x^2)=0

<=> x(x-1)(7x+3)=0

<=> x=0;x=1;x=-3/7

29 tháng 9 2017

a,  2x^3+3x^2-2x-3=0

<=> 2x^3-2x^2+5x^2-5x+3x-3=0

<=> 2x^2(x-1)+5x(x-1)+3(x-1)=0

<=> (x-1)(2x^2+5x+3)=0

<=> (x-1)(2x^2+2x+3x+3)=0

<=> (x-1)[2x(x+1)+3(x+1)]=0

<=> (x-1)(x+1)(2x+3)=0

<=>x=1;x=-1;x=-3/2

<=>